(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
The aim of my publication is to make a biographical sketch of the most influential and innovative surgeons in modern surgery, based on scientific positivism. The period on study is between 1.850 and 2.000